SUMBER-SUMBER PENDIDIKAN ISLAM (Penalaran, Pengalaman, Intuisi, Ilham dan Wahyu) - ., Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract: Islam with western science differ in assessing either the truth or the source, so the inequality of knowledge paradigm used will produce a way of thinking different perspective. Islam supported by revelation will certainly have a different attitude to Western civilization that sees revelation as something that is not scientific. In the epistemological level, the difference is clearly visible perspective when faced with the question of the sources of knowledge. The word is taken from the knowledge of the English language